(ADP-ribosyl)hydrolases: structure, function, and biology - Rack, JGM; Palazzo, L; Ahel, I (Cold Spring Harbor Laboratory Press, 2020)
ADP-ribosylation is an intricate and versatile posttranslational modification involved in the regulation of a vast variety of cellular processes in all kingdoms of life. Its complexity derives from the varied range of different chemical linkages, including to several amino acid side chains as well as nucleic acids termini and bases, it can adopt. In this review, we provide an overview of the different families of (ADP-ribosyl)hydrolases. We discuss their molecular functions, physiological roles, and influence on human health and disease. Together, the accumulated data support the increasingly compelling view that (ADP-ribosyl)hydrolases are a vital element within ADP-ribosyl signaling pathways and they hold the potential for novel therapeutic approaches as well as a deeper understanding of ADP-ribosylation as a whole.